(3UQa GdYfGjI aj cTa GdcaGjIs - (3YHO Gddg Hf eMeO GdcQOi GdHjJhTis; (3YHO Gddg Hf eMeO GdcQOj GdHjJhTs ((3eMeO Hf eHGQc Hf MeO GdEMSGFi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CHOY dfG GdMQha hGdeYGfi hHYO ajbhd GdabjQ GdHjJhT Gfi deG fXeJ efXheJi caGjI GdeYGfi ai MQha GdeYGfi s
(3BNQgG (B:s
(3adG jbGd dCNQ GdcJGH eKdkG (B: (3gPG ceGd GdcJGH dCf ceGd GdTF YHGQI Yf LejY CLRGFg Hd jbGd gPG JeGe GdcJGH s
(3HChdg Jedc dfGSNg SfI(B1225s
(3HgG fXGe GdJYbjHIs
(3aQZ ef eDda (B1198 s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdfMhs